Assessing the fishing footprint using data integrated from different tracking devices: Issues and opportunities. (October 2016) - Russo, T.; D'Andrea, L.; Parisi, A.; Martinelli, M.; Belardinelli, A.; Boccoli, F.; Cignini, I.; Tordoni, M.; Cataudella, S.
Highlights: Vessel tracking devices (e.g. VMS/AIS) are widely used to monitor fishing activity. Data from these devices allow the estimation of fishing pressure indicators. VMS and AIS data were compared on a large national fleet. Important differences in spatial, temporal and fleets coverage were detected. Combined use provides a significant improvement of indicators computation. Abstract: Different tracking devices are currently used to record the activity of fishing vessels in space and time and to analyse the pattern of fishing effort with respect to sea substrates, resources, or socio-economics factors. Among these devices, the Vessel Monitoring System (VMS) and the Automatic Identification System (AIS) represent the most interesting and fertile data sources for fisheries investigations but an integration of these two sources was never explored. Two large VMS and AIS datasets, covering the activity of the Italian fishing vessels with length-over-all ≥15 m for the whole year 2012, were used to perform the first assessment of the features characterizing each data source, and ultimately the properties of the estimators of ecological indicators of fishing pressure obtained using these data. In this way, a dataset related to five vessels equipped by a third high frequency device (the Fishing Observing System) was used as reference for a comparative analysis of fishing activity as reconstructed by VMS and/or AIS. Moreover, the ecological indicator 5 of fishing pressure as spatial extent of fishing activity (defined within the Data Collection Framework for Fisheries—DCF) was used as a reference to test the separate and integrated usage of VMS and AIS data. Results evidenced important differences in spatial, temporal and fleet coverage between VMS and AIS. Namely, VMS is affected by a lower frequency with respect to AIS but covers a larger portion of the fleet. Furthermore, AIS mainly operates near the harbours, so that offshore activity is underrepresented. The integration of VMS and AIS data, however, allows valorising the strengths and minimizing the limits of each source. In fact, the assessment of the total spatial extent of fishing activities (as captured by the DCF indicator 5) is significantly improved by the integrated usage of VMS and AIS data.